TATA KELOLA REKAM MEDIS BERBASIS TEKNOLOGI INFORMASI DALAM PENANGANAN KERAHASIAAN DAN KEAMANAN DATA PASIEN DENGAN METODE KRIPTOGRAFI - Aellen Sarce Joel; Falaah Abdussalaam; Yuyun Yunengsih (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Confidentiality and security of patient data in hospitals is very important and data protection is mandatory. In this study, a problem was found, namely that there was no guarantee of protecting the security and confidentiality of patient data which allowed the data to leak. This study aims to design an information technology-based medical record governance system to maintain the confidentiality and security of patient data. The research technique uses a qualitative methodology with a descriptive approach and collects data through observation, interviews and literature studies. While the waterfall method is used to develop the system through the stages of needs analysis, design, implementation and testing. The system design was carried out using Microsoft Visual Studio 2010 which was implemented using the AES (Advanced Encryption Standard) Rijndael cryptography algorithm. The results of the research that has been done are obtained that the existence of information technology-based medical record governance in handling the confidentiality and security of patient data using AES cryptography can increase the confidentiality and security of patient data in medical record management.